Mechanical engineering education - Davim, J. Paulo (Iste Ltd ; John Wiley &, 2012)
It addition to its role in the manufacturing and maintenance of mechanical systems. mechanical engineering has recently moved into cutting-edge subjects such as nanomechanics and nanotechnology, mechatronics and robotics, computational mechanics, biomechanics, alternative energies, as well as aspects related to sustainable mechanical engineering.